(untitled) (Acta Scientiarum. Technology, 2024)
This study analyzed biodiesel blends using sensors constituted by SnO2 pellets with gold interdigitated contacts deposited on the surface. Tin dioxide was synthesized by the polymeric precursor method with further calcination treatment at 500°C, conformed and sintered at three temperatures to form three different samples: 700°C (Sn1), 900°C (Sn2) and 1100°C (Sn3). The samples were analyzed by X-Ray Diffraction, FEG-SEM (Field Emission Gun - Scanning Electron Microscopy), Raman spectroscopy, and electrical measurements. Results confirmed the formation of rutile-type tetragonal cassiterite phase, with quasi-spherical particles a moderate degree of heterogeneity in particle size 30-90 nm). Raman vibrational modes and infrared spectrum also confirmed the presence of tin oxide in high purity rutile phase. Sensorial measurements showed high sensitivity, response, and recovery time in tests with biodiesel/ethanol mixtures, allowing to distinguish between blends with a wide range of composition and serving as a potential device to detect adulterated fuel.